1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Complex Analysis (i need help,immediately)

  1. Oct 13, 2009 #1
    Please help me with them problems:
    1) if z^3=1, show that (1-z)(1-z^2)(1-z^4)(1-z^5)=9, zEC

    2) if cos(x)+cos(y)+cos(t)=0, sin(x)+sin(y)+sin(t)=0 show that cos(3x)+cos(3y)+cos(3t)=3cos(x+y+t)

    3)show that, the roots the equations (1+z)^(2n) +(1-z)^(2n)=0, nEN, zEC are given by the relation z=itan((2κ+1)π)/4n), κ=0,1,...,n-1
  2. jcsd
  3. Oct 13, 2009 #2


    User Avatar

    Staff: Mentor

    You must show some effort of your own, before we can offer tutorial help. How would you start working on each of these?
  4. Oct 13, 2009 #3
    Problem (1), (3): i have no idea
    Problem (2): question...cos(x)cos(y)cos(t)-cos(x)sin(y)sin(t)-sin(x)cos(y)sin(t)-sin(x)sin(y)cos(t)=cos(y) (cos(t) cos(x)-sin(t) sin(x))-sin(y) (sin(t) cos(x)+cos(t) sin(x))=cos(x+y+t)? if answer=yes, i'm ok with this problem, i solve this problem!

    Please help me with the problems (1), (2)
  5. Oct 13, 2009 #4


    Staff: Mentor

    You mean problems 1 and 3.

    For 1, if z3 = 1, then z must be one of the complex cube roots of 1. All three have magnitude 1, but different args (angles). One of them has an arg of 2pi/3. Maybe you can come up with the other two.

    For each one, evaluate (1-z)(1-z2)(1-z4)(1-z5), and see what you get. That's how I would approach it.

    For 3, I don't have any insights right now, but I would start playing with it. For example, I would check that z = i tan(1/4) is a solution of your equation. (This is the solution for K = 0.)
  6. Oct 13, 2009 #5


    User Avatar
    Science Advisor
    Homework Helper

    For 1) there are three complex roots of z^3=1, as Mark44 said. But z=1 doesn't work since (1-z)=0. So you must mean one of the other ones. But there is a simple way to do it. Since z^3=1, z^4=z and z^5=z^2. So you've now got (1-z)^2*(1-z^2)^2. Since |z|=1 and z(z^2)=1 that means z^2=z* (*=complex conjugate). Now you've got ((1-z)(1-z*))^2. If you expand that one of the parts is z+z*. Can you show that's (-1) for z a complex root of z^3=1?
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook